Identification and validation of clinically meaningful benchmarks in the 12-item Multiple Sclerosis Walking Scale. (September 2017) - Goldman, Myla D; Ward, Melanie D; Motl, Robert W; Jones, David E; Pula, John H; Cadavid, Diego
Background: The 12-item Multiple Sclerosis Walking Scale (12-MSWS) is a validated questionnaire which assessed walking function; it has been widely adopted in multiple sclerosis (MS) clinical research. Objective: Identify and validate clinically meaningful 12-MSWS benchmarks in MS. Methods: Cross-sectional study of 159 MS patients permitted identification of clinically meaningful 12-MSWS benchmarks based on their relationship to real-life anchors. Identified 12-MSWS benchmarks were then validated in a second population of 96 subjects using measures of ambulation, cognition, and patient-reported outcomes. Results: 12-MSWS score of 0–24.99 was associated with working outside the home and assistance-free mobility; 25–49.99 was associated with gait disability and difficulty doing housework; 50–74.99 was associated with unemployment, government healthcare, cane use, and difficulty performing instrumental activities of daily living (IADLs); and 75–100 was associated with change in occupation due to walking, mobility impairment requiring bilateral assistance, and inability to perform IADLs. During the validation step, strong linear associations were identified between 12-MSWS benchmarks and other MS-related disability outcome measures, including ambulatory and non-ambulatory measures. Conclusion: We have identified clinically meaningful 12-MSWS benchmarks which define four groups differentiated by increasing levels of mobility impairment and associated loss of functional independence. These data provide insight into how 12-MSWS translate to meaningful functional limitations in MS.